Bibliometric analysis of studies on the treatment of hemifacial spasm - Fang, Li-Jun; Wang, Chen-Yao (Frontiers in Neurology, 2022)
Objective Hemifacial spasm (HFS) is a common neurological disorder of the brain, which is difficult to treat. Most patients are distracted by it and are unable to work or study normally, which seriously affects their physical and mental health. However, there are a few bibliometric studies on it. This paper searched the articles on HFS using a bibliometric approach. Method Articles about HFS were retrieved from the Web of Science (WoS) Core Collection database. We employed the Visualization of Similarities (VOS)viewer to analyze these publications. Results A total of 645 reviews or articles in English were retrieved from WoS. In this study, we found that the number of publications showed a rising trend and China is the most active in searching the treatment of HFS. About keywords, neurosciences and neurology was searched (422 times) keyword, followed by hemifacial spasm (420 times) and surgery (320 times). By assessing the organizations, Shanghai Jiao Tong University published the most papers (8.68%), followed by Sungkyunkwan University (3.26%) and Baylor College Medicine (2.64%). A total of 247 journals have delivered publications on the treatment of HFS, World Neurosurgery (44 papers) published the largest number of articles. Conclusion The annual publications have increased with a fluctuating tendency. More researchers were taking an interest in HFS. This study helped us find out the hotspot and trend in research about facial spasm treatment.